Photocatalytic and theoretical study of CoS nanoparticles for sustainable dye removal from wastewater - Heba M. El Sharkawy; Ghada E. Khedr; Esraa M. El-Fawal (Scientific Reports)
Abstract Photocatalytic degradation has emerged as a promising approach for addressing dye-laden wastewater from industrial effluents. In this study, a cost-effective cobalt sulfide (CoS) photocatalyst was synthesized via a simple precipitation method and employed for the visible-light-driven degradation of cationic methylene blue (MB) and anionic methyl red (MR) dyes. The as-prepared CoS was characterized using XRD, HR-TEM, FE-SEM, DRS, and PL techniques, revealing a hexagonal phase structure, uniform spherical morphology with particle sizes of 15–22 nm, a mesoporous surface with a BET-specific surface area of 33.6 m²·g⁻¹, and a narrow band gap of 1.6 eV. Under optimized conditions, CoS demonstrated excellent photocatalytic performance, achieving 97.7% degradation of MB and 75.3% degradation of MR within 90 min under visible light. Kinetic analysis showed a pseudo-first-order reaction with rate constants of 0.03 min⁻¹ for MB and 0.01 min⁻¹ for MR. Density functional theory (DFT) simulations further elucidated the adsorption configurations and energetics of both dyes on the CoS (100) surface, revealing stronger adsorption of MB compared to MR. These findings highlight the potential of CoS as an affordable and efficient photocatalyst for sustainable wastewater remediation applications.